Cosmology with nonminimal derivative couplings - Amendola, Luca (Arxiv, 1993)
We study a theory which generalizes the nonminimal coupling of matter to gravity by including derivative couplings. This leads to several interesting new dynamical phenomena in cosmology. In particular, the range of parameters in which inflationary attractors exist is greatly expanded. We also numerically integrate the field equations and draw the phase space of the model in second order approximation. The model introduced here may display different inflationary epochs, generating a non-scale-invariant fluctuation spectrum without the need of two or more fields. Finally, we comment on the bubble spectrum arising during a first-order phase transition occurring in our model.
Gesehen am 21.11.2017